Technology and the geography of the foreign exchange market. (March 2023) - Eichengreen, Barry; Lafarguette, Romain; Mehl, Arnaud; Ferrari Minesso, Massimo
Highlights: Cable connections cut the costs of trading currencies locally. They increase the share of offshore currency transactions. They also attenuate the effect of existing spatial frictions. Cable connections boosted the share in global turnover of London by as much as one-third. Abstract: We analyze the impact of technology on the production and trade in services, focusing on the location of foreign exchange transactions and the effect of submarine fiber-optic cable connections. Cable connections between local markets and major financial centers reduce the costs of trading currencies locally and increase the share of currency transactions taking place in the issuing country. But they also attenuate the effect of existing spatial frictions that prevent transactions from moving offshore to take advantage of agglomeration economies and thick-market advantages of major financial centers. In practice, this second effect dominates. Our estimates suggest that the advent of cable connections boosted the share in global turnover of London, the world's largest trading venue, by as much as one-third.